Age, Chemotherapy Frequency, and Nutritional Status as Predictors of Chemotherapy-induced Anemia in Rural Populations - Cahyono, Hendra Dwi; Martiana, Ina; Kusumasa, Fitri; Fatarona, Anita; Tursina, Hella Meldy; Correia Ximenes, Joao Manuel (Universitas Tribhuwana Tunggadewi, 2025)
Chemotherapy is a primary treatment modality for cancer, but it often results in adverse effects such as anemia due to decreased hemoglobin levels. Factors including age, chemotherapy frequency, and nutritional status may influence hemoglobin levels, particularly in rural areas with limited healthcare resources. To examine the relationship between age, chemotherapy frequency, and nutritional status and hemoglobin levels among cancer patients undergoing chemotherapy in a rural setting. This cross-sectional, correlational study involved 154 cancer patients undergoing chemotherapy at Baladhika Husada Hospital, Jember, from July to September 2024. Data were collected through patient interviews, the Mini Nutritional Assessment (MNA), and hemoglobin test results. Bivariate analysis using Spearman’s rank correlation was conducted to assess associations among variables. The majority of participants were aged 46–55 years (42.8%), had received 1–3 chemotherapy cycles (57.1%), and were at risk of malnutrition (45.5%). A significant association was found between age (p = 0.009, r = 0.191) and nutritional status (p = 0.014, r = 0.178) and hemoglobin levels. No significant association was found between chemotherapy frequency and hemoglobin levels (p = 0.60). Age and nutritional status are significantly associated with hemoglobin levels in cancer patients undergoing chemotherapy, while chemotherapy frequency is not. These findings highlight the need for individualized care and nutritional interventions, particularly for elderly patients in rural areas, to mitigate the risk of Chemotherapy-Induced Anemia